Le contrôle exercé sur la conjointe : comparaison de quatre groupes d’hommes - Roy, Benoît; Rondeau, Gilles (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1997)
This paper presents the results of an exploratory study on the control exerted by men over their spouse. Four groups of 15 men each, were compared: 1) men with no criminal record and who had volontarily taken part in a community program for violent men; 2) men accused of spouse abuse, exclusively; 3) men accused of spouse abuse and other crimes; 4) men selected at random from the community. The type of sample was non probabilistic. Three questionnaires were administered: 1) a demographic questionnaire 2) the "Abusive Behavior Inventory" (Shepard and Campbell, 1992) and 3) the "Psychological Maltreatment of Women Inventory" (Tolman, 1989). The results demonstrated that the control group (group 4) displayed "stability" in comparaison with the groups of accused men (groups 2 and 3) where important difficulties and "marginality" were observed. "Non accused" spouse abusers (group 1) obtained middle ranged scores. Scores from the four sub-scales in the two attitudinal inventories corrrelated significantly and were in the predicted direction. As the level of psychological or physical abuse increased, so did the desire to dominate and isolate women. Given the small sample size and the quasi-experimental nature of the design, the results are not considered as definitive; however, they provide directions for future research.